Entrepreneurship Education as a lever for youth employment: lessons learned for Algeria through the Finnish Experience - Medfouni, Fairouz (Journal of Excellence for Economics and Management Research, 2026)
This study aims to analyze the Finnish experience in entrepreneurship education, as it is considered one of the most successful international models in this field, and to identify lessons that Algeria could apply to develop its own entrepreneurship education. To achieve the research objectives, a descriptive approach was adopted to describe the variables, and an analytical approach was used to analyze the current state of entrepreneurship education in Finland. The research yielded a number of findings, the most significant of which is that the success of entrepreneurship education in Finland stems from its adoption of an integrated and comprehensive educational policy starting from elementary school, in addition to its reliance on supportive programs based on collaboration with the business sector. For Algeria to benefit from this experience, it must undertake numerous reforms in its educational curricula while ensuring the training of teachers in the field of entrepreneurship.